Digital Islamic Social Investment: Integrasi Zakat Produktif dalam Penguatan UMKM Berbasis Maqashid Syariah dan Sustainable Development - Neli Nur Hidayati (FEBI IAIN Langsa, 2026)
This research aims to develop a conceptual framework for Digital Islamic Social Investment as an integrative model for strengthening productive zakat-based MSMEs that is in line with sharia maqashid and the Sustainable Development Goals (SDGs). Although the literature on productive zakat, Islamic social finance, and digital finance is growing rapidly, there is still a conceptual gap in the form of the absence of an integrative model that systematically links productive zakat, digital infrastructure, and the sustainable development agenda in a single comprehensive theoretical framework. This research uses a conceptual research approach through systematic literature review and theoretical synthesis of literature related to productive zakat, Islamic social investment, financial inclusion, sharia maqashid, and SDGs. The conceptual findings of this study formulate three main elements of Digital Islamic Social Investment, namely capital injection, capacity building, and social return orientation, which are strengthened by the digital ecosystem as an infrastructure for collection. transparency, data-driven monitoring, and impact evaluation. This framework explains how productive zakat can be repositioned as a social investment instrument that encourages business strengthening, increasing financial inclusion, and sustainable economic empowerment. Theoretically, this research contributes to the development of an integrative model of technology-based Islamic social finance that expands the zakat discourse from a charitable approach to a social investment paradigm oriented towards sustainability and inclusive development.